2020
DOI: 10.3390/ijerph17207412
|View full text |Cite
|
Sign up to set email alerts
|

Association between Urinary Triclosan and Serum Testosterone Levels in U.S. Adult Males from NHANES, 2011–2012

Abstract: Triclosan was introduced into the market in the 1970s and has since been used as an antimicrobial agent in a diverse array of consumer and personal care products. Although it has been widely used over a number of years, there is growing concern and debate over its safety and efficacy and its potential as an endocrine disruptor. Although prior animal toxicology studies have shown an association between triclosan and decreased testosterone levels, human studies have been limited, particularly for adult men. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Potential multicollinearity among the predictor variables was assessed by examining the variance inflation factors' (VIF) diagnostic statistics. Although there is no formal VIF value for detecting multicollinearity, values of VIF 10 or above are often indicative of multicollinearity [48]. The unstandardized coefficients with a 95% confidence interval (95% CI) obtained from the models were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Potential multicollinearity among the predictor variables was assessed by examining the variance inflation factors' (VIF) diagnostic statistics. Although there is no formal VIF value for detecting multicollinearity, values of VIF 10 or above are often indicative of multicollinearity [48]. The unstandardized coefficients with a 95% confidence interval (95% CI) obtained from the models were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing from prior research, a comprehensive range of potential confounders was considered, including race/ethnicity (Mexican American, other Hispanic, non-Hispanic White, non-Hispanic Black, other race), level of education (less than high school, high school and above), body mass index (underweight, normal, overweight, obese), time of blood draw (morning, afternoon, evening), season of collection (November 1 through April 30, May 1 through October 31), household poverty-income ratio (<1, ≥ 1), and cotinine levels (tobacco exposed or unexposed). The categorization of tobacco exposure was based on the limits of detection (LOD) of cotinine, set at 0.015 ng/mL …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, a study on male Wistar rats demonstrated the absence of effects of TCS in the Hershberger assay, as well as on the parameters that were evaluated in the reproductive toxicity study [ 150 ]. Another work on serum testosterone levels in human adult males found that TCS did not reduce testosterone levels [ 151 ]; low-dose TCS exposure was not associated with risks of abnormal semen quality in a study on 406 men from a reproductive clinic [ 152 ]. In a study on children and adolescents aged 6–19 years, little association of TCS and testosterone levels was found [ 153 ].…”
Section: Toxicity Studies On Tcsmentioning
confidence: 99%